DEVELOPING PROBLEM-SOLVING AND INNOVATIVE THINKING THROUGH TECHNOLOGY-BASED ART PROJECTS - Sharipova Gulshoda Bahriddinovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article examines how technology-based art projects can enhance students’ problem-solving skills and innovative thinking. Integrating technology into art education allows students to experiment creatively, analyze challenges, and develop practical solutions. The study highlights that project-based approaches in technology-supported art activities increase engagement, foster critical thinking, and cultivate both artistic and technological competencies. Understanding these connections helps educators design learning experiences that encourage innovation and effective problem-solving.